Influence of Tissue Type on the Bacterial Diversity and Community in Pork Bacon - Gong, Wenjuan; Zhu, Yan; Shi, XiXiong; Zhang, Weibing; Wen, PengCheng (Frontiers in Microbiology, 2021)
In current study, bacterial diversity and community in different tissues of pork bacon were measured using high-throughput sequencing. In total, we identified six phyla and 111 bacterial genera. Among them, three dominant genera (Staphylococcus, Acinetobacter, and Macrococcus) were shared by all bacon samples. The linear discriminant analysis showed that 24 bacterial taxa signiﬁcantly differentiated between the tissues. Results of Nonmetric Multidimensional Scaling and redundancy analysis showed that physicochemical characteristics of the tissue prominently structured the bacterial communities. Network analysis also illustrated that tissue type was an important factor impacting the bacterial interactions in different types of tissue. The results of current study can add valuable insights to the traditional homemade pork bacon.